2023
DOI: 10.3390/ijns9030042
|View full text |Cite
|
Sign up to set email alerts
|

Alberta Spinal Muscular Atrophy Newborn Screening—Results from Year 1 Pilot Project

Abstract: Spinal muscular atrophy (SMA) is a progressive neuromuscular disease caused by biallelic pathogenic/likely pathogenic variants of the survival motor neuron 1 (SMN1) gene. Early diagnosis via newborn screening (NBS) and pre-symptomatic treatment are essential to optimize health outcomes for affected individuals. We developed a multiplex quantitative polymerase chain reaction (qPCR) assay using dried blood spot (DBS) samples for the detection of homozygous absence of exon 7 of the SMN1 gene. Newborns who screene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…NBS for SMA was begun on 28 February 2022 and included a qPCR screening assay to detect the absence of SMN1 exon 7, which was multiplexed with an already established SCID qPCR assay allowing for a smooth cost-effective implementation. The results of screening 47,005 newborns during the first year of the program (prevalence of 1:9401) were recently reported [ 369 ]. NBS for classical galactosemia (galactose transferase deficiency—GALT) has been ongoing since April 2019, using a two-tier screening approach, which secondarily identifies infants with glucose-6-phosphate dehydrogenase (G6PD) deficiency.…”
Section: Resultsmentioning
confidence: 99%
“…NBS for SMA was begun on 28 February 2022 and included a qPCR screening assay to detect the absence of SMN1 exon 7, which was multiplexed with an already established SCID qPCR assay allowing for a smooth cost-effective implementation. The results of screening 47,005 newborns during the first year of the program (prevalence of 1:9401) were recently reported [ 369 ]. NBS for classical galactosemia (galactose transferase deficiency—GALT) has been ongoing since April 2019, using a two-tier screening approach, which secondarily identifies infants with glucose-6-phosphate dehydrogenase (G6PD) deficiency.…”
Section: Resultsmentioning
confidence: 99%
“…The review identified 37 cohort studies of newborn screening for SMA [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. No RCTs of newborn screening were identified.…”
Section: Resultsmentioning
confidence: 99%
“…Cohort studies relating to newborn screening programmes for SMA were identified from the following 17 countries ( Table 1 ): the UK [ 9 ], Belgium [ 10 , 11 , 12 ], Germany [ 13 , 14 , 15 , 16 , 17 , 18 ], Italy [ 19 , 20 ], Latvia [ 21 ], Portugal [ 22 ], Poland [ 23 ], Ukraine [ 24 ], Norway [ 25 ], Australia [ 26 , 27 , 28 , 29 ], the USA, Canada [ 30 , 31 , 32 ], Brazil [ 45 ], Japan [ 46 , 47 , 48 , 49 , 50 ], Taiwan [ 51 , 52 ], China [ 53 , 54 , 55 ] and Russia [ 56 , 57 ]. The USA screening programmes were reported for several US states: California [ 33 ], Georgia [ 34 ], Kentucky [ 35 ], Massachusetts [ 36 , 37 ], New York [ 38 , 39 , 40 ], North Carolina [ 41 ], Wisconsin [ 42 ], Utah [ 43 ] and Ohio [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…SMA newborn screening has recently been implemented in many provinces and territories across Canada, which will help to provide more accurate incidence estimates of SMA by geographic location. 21,25 One recent study by Kernohan and colleagues included data from the first year of SMA newborn screening in Ontario; 139,900 newborns were tested and five were confirmed with SMA, which represented a birth prevalence of 1 in 27,960 live births during 2020-2021. 26 This birth prevalence is in line with the combined rates from CPSP and CNDR observed in the current study of 1 in 25,951.…”
Section: Discussionmentioning
confidence: 99%